Development of Paving Block Structure Variation for Traffic Safety and Comfort - Muhamad Yusuf; P Pratikso; Rachmat Mudiyono; Totti Aditya Susanto; Zoggy Ardi Eka Saputra (JACEE (Journal of Advanced Civil and Environmental Engineering), 2024)
Urban traffic congestion worldwide leads to air pollution, increased vehicle noise, and longer travel times for both private and public transit. Congestion adversely affects the well-being of road users and urban residents, and traffic accidents are closely linked to congestion. Traffic composition, road infrastructure, environmental conditions, vehicle design, and human behavior can cause congestion. Concrete block pavement is a practical option for improving traffic safety and increasing driving comfort at intersections with traffic lights. Concrete block paving roads are a cost-effective engineering solution for residential, commercial, municipal, and industrial environments. The study uses the Autocad program to create a simulation of a paved surface and a research tool to analyze the model of the research subject. Results indicate that pavement types subjected to higher loads exhibit more deformation than those under lower loads. Pavements with higher weights are more likely to deform, with the Herringbone 90° pavement type able to withstand a maximum load of 2100 kg and exhibiting the highest load deformation rate of 0.21 cm/kg. The study investigates the load-bearing abilities of different pavement kinds and patterns. The Basketweave pavement type has the lowest load capacity at 2077.9 kg and the lowest load deformation rate of 0.41 cm/kg.